Teachers’ perception of school based continuous professional development in Zambia - Muyunda, Gift (Association for Scientific Computing Electrical and Engineering(ASCEE), 2023)
This study aimed to explore teachers' perceptions, practices, and challenges in Zambia school based teacher professional development programs. The survey sample consisted of four primary schools, four school principals, four schools’ continuous professional development (CPD) coordinators, one DEBS official, and 198 teachers. The major findings show that there is a positive perception of teachers toward school-based CPD programs. In addition, the results show that even though teachers have positively perceived school-based CPD well, the practice of CPD program implementation is at a low level in secondary schools. Furthermore, the study findings indicated the lack of teachers' support from school management and supervisors and lack of collaboration with teachers and school leaders were among the factors that affected the implementation of the CPD program. The study also shows that teachers with more teaching experience positively perceive the school-based CPD programs, and teachers with degree holders practice more CPD activities than diploma holders.